On the link volatility between tin price and stock - Munandar, Adis Imam; Siregar, Hermanto; Andati, Trias; Anggraeni, Lukytawati (IJRDO - Journal of Business Management, 2016)
The influence of commodity prices which affects the stock market has been investigated in previous researchers. This research aims to examine the volatility effect of tin commodity prices to the company’s stock price. Vector Error Correction Model (VECM) is employed with monthly data from 2003 to 2015. The results showed that the price of tin has a relationship with the equity of PT Timah Tbk, Malaysia Smelting Corporation and Yunnan Tin Company Limited which indicates the existence of financialization commodity market